The cultural and political legacy of Anne de Bretagne : negotiating convention in books and documents - Brown, Cynthia Jane (Gallica (Woodbridge (Suffolk, England)), 2010)
As duchess of Brittany [1491-1514] and twice queen of France [1491-98; 1498-1514], Anne de Bretagne set a benchmark by which to measure the status of female authority in Europe at the dawn of the Renaissance. Although at times a traditional political pawn, when men who ruled her life were involved in reshaping European alliances, Anne was directly or indirectly involved with the principal political and religious European leaders of her time and helped define the cultural landscape of her era. Taking a variety of cross-disciplinary perspectives, these ten essays by art historians, literary specialists, historians, and political scientists contribute to the ongoing discussion of Anne de Bretagne and seek to prompt further investigations into her cultural and political impact. At the same time, they offer insight of a broader nature into related areas of intellectual interest - patronage, the history of the book, the power and definition of queenship and the interpretation of politico-cultural documents and court spectacles - thereby confirming the extensive nature of Anne's legacy. CYNTHIA J. BROWN is Professor of French at the University of California, Santa Barbara.